Virulence Determinants of Acinetobacter baumannii Isolated from Different Infections in Baghdad Hospitals - Sajad Numan; Fitua Al-Saedi; Israa Burhan; Mojtaba Mohammadzadeh Vazifeh (College of Pharmacy / Mustansiriyah University, 2024)
Acinetobacter baumannii is an essential pathogenic bacteria cause nosocomial infections worldwide. The current work aimed to characterize several virulence factors in Acintobacter baumannii isolated from diverse clinical specimens in Baghdad. Clinical samples including sputum, blood, urine, CSF and wound swabs were collected from patients who were admitted to hospitals in Baghdad. Identification of Acinetobacter baumannii isolates was performed using Vitek 2 system. Phospholipase (plcN) and elastase (lasB) genes were identified using Polymerase chain reaction (PCR) technique. Other virulence factors such as motility, biofilm formation,hemolysin  production were screened. Sixty-nine isolates were identified as Acinetobacter baumannii. The isolates were screened for Phospholipase (plcN) and elastase (lasB) production.The results of amplification revealed that out of the total  isolates, 18 (26.6%) isolates included both (plcN) and (lasB) genes, 18(26.6%) isolates included only (plcN) and 23(33.3%)  isolates have only (lasB). Sixty (86.9%) isolates were positive for biofilm formation, 8 (11.6%) isolates indicated intermediate biofilm producers and 52(75.4%) isolates were weak biofilm producers. Sixty six  A.baumannii isolates were motile on Nutrient agar (0.3%). Sixteen isolates were intermediate motile and 50 were highly motile. Positive association was found between the biofilm formation capacity and surface associated motility. Fifty-seven isolates showed hemolysis on Blood agar on the second day of the incubation. Of these, 48 (69.56%) isolates show β -hemolysis and 9 (13.04%) isolates show α-hemolysis,